Preparação e caracterização de poliuretanos com diferentes quantidades de óleo de baru (Dipteryx alata Vog.) - Almeida, Elizabeth Luiza de (2015)
The development of new materials obtained from natural renewable sources has been growing, materials that can show different characteristics from materials produced by petrochemical industry. Vegetable oils are good sources to produce polymeric materials, besides being biodegradable. The Baru Oil can be a renewable raw material from the Brazilian cerrado, with high unsaturation percentage. The ann of this work was the study of polyurethane foam obtained from pre-polymer and polyol (produced by Cequil Industry) with different quantities of baru saponified oil (5%, 15%, 24% e 29%) (m/m), and the characterization with TG/DSC, FTIR, TG-DSC coupled with FTIR in dry air and N2 atmospheres and Swelling Index and Zn2+ adsorption. FTIR spectrum showed the bands at 1743 cm-1 (C=O), characteristics of polyol, at 3320 cm-1 hydroxyl groups, at 2271 cm-1 and 1596 cm-1 characteristics bands of isocyanate groups of the PP. The TG-DSC curves in N2 and air indicated different profiles, especially the formation of more stable intermediates on the oxidation of these materials in air atmosphere. It was found that the thermal stability decreases as the OB weight increases. The quantity of heat obtained by DSC curves and the weight loss obtained by TG curves, indicates an OB saturation in 24% (m/m). Using the FTIR method, the study of volatile products presented characteristic peaks of water, CO2, CO and ethanol. With the increase of OB, higher water absorption of PU, in 29% of swelling index 91.1% for 1440 minutes. Further, the polyurethane higher water absorption prevented Zn2+ adsorption in a possible application in chemical decontamination of industrial wastewater. From these results, we observed the polyurethane formation with different characteristics because of the presence of OB.